2014
DOI: 10.1111/mec.12713
|View full text |Cite
|
Sign up to set email alerts
|

Divergent immunity and energetic programs in the gills of migratory and resident Oncorhynchus mykiss

Abstract: Divergent life history strategies occur in steelhead or rainbow trout Oncorhynchus mykiss, and many populations produce both migrant (anadromous fish that move to the ocean after rearing) and resident (do not migrate and remain in fresh water) individuals. Mechanisms leading to each type are only partially understood; while the general tendency of a population is heritable, individual tendency may be plastic, influenced by local environment. Steelhead hatchery programmes aim to mitigate losses in wild stocks b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 66 publications
1
42
1
Order By: Relevance
“…Despite the comprehensiveness of our screening approach, an unknown viral agent may have been present within these fish. Alternatively, expression patterns may be a relic of cleared, latent, or anticipated viral infection: freshwater-resident Oncorhychus mykiss have shown overexpression of antiviral transcripts relative to out-migrating smolts, suggesting a modulation of immune defences towards viral pathogens in freshwater (Altizer et al ., 2011; Sutherland et al ., 2014). Enhanced expression of immune transcripts, including both cellular and humoral responses, have been documented in sockeye salmon during the spawning migration, corresponding to shifts in environmental and biotic factors (Evans et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the comprehensiveness of our screening approach, an unknown viral agent may have been present within these fish. Alternatively, expression patterns may be a relic of cleared, latent, or anticipated viral infection: freshwater-resident Oncorhychus mykiss have shown overexpression of antiviral transcripts relative to out-migrating smolts, suggesting a modulation of immune defences towards viral pathogens in freshwater (Altizer et al ., 2011; Sutherland et al ., 2014). Enhanced expression of immune transcripts, including both cellular and humoral responses, have been documented in sockeye salmon during the spawning migration, corresponding to shifts in environmental and biotic factors (Evans et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…; Sutherland et al . ); however, the influence of differential expression on the brain is unknown. Genomic regions of interest include chromosomes OMY12 and OMY14, which appear to be hot spots for migration‐related QTL in this population (Hecht et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Robertson & McCormick ; Sutherland et al . ) and gene network analysis (Filteau et al . ) have demonstrated differential gene expression between fish with different life histories.…”
Section: Introductionmentioning
confidence: 99%
“…mykiss . Sutherland et al () compared gene expression in the gills of migrating and non‐migrating hatchery‐reared individuals. They found that migrants (presumably in preparation for smoltification) overexpressed gene transcripts related to energy generation (oxygen‐transport proteins and mitochondrion components) and ion transport.…”
Section: Closing Observationsmentioning
confidence: 99%
“…Fish and Wildlife Service, has contributed significantly to recent work on the genomic underpinning of differences in gill function between migratory and non-migratory O. mykiss. Sutherland et al (2014) compared gene expression in the gills of migrating and non-migrating hatchery-reared individuals. They found that migrants (presumably in preparation for smoltification) overexpressed gene transcripts related to energy generation (oxygen-transport proteins and mitochondrion components) and ion transport.…”
Section: Closing Observationsmentioning
confidence: 99%